Success factor to be an excellent project manager - Nurul Nadia, Abd Karim (2010)
In general,the project manager is responsible for the overall success of the project.In some companies,this person might be called a Project Coordinator,or a Team Leader,however,the key aspect is that the person is responsible for ensuring the success of the project.Now a day there is much project delay around Kuala Lumpur.The major factor of project delay is because of poor management of project manager.Project manager who is responsible to handle the entire construction project,to finding the right project manager is therefore a major task in project implementation.The aims of this study are to identify the selection factor to be a good project manager,to identify the success factor to be an excellent project manager and to analyze the success factor to be an excellent project manager.The major responsibility of the Project Manager will be to manage and deliver projects, as assigned.The individual will bring strong planning and process skills to the team and will have management accountability for the definition and execution of the project plans including project initiation, planning,execution,controlling,staffing, scheduling, monitoring and closing out the project.The project manager will manage project dependencies and team and stake holder relationships as it relates to the project and ensure timely and effective communication with the project team and with the project stakeholders. The questionnaires were distributed to the contractor, client and consultant by hand around Kuala Lumpur.The questionnaire consists of two sections;first section are identify the success factor to be an excellent project manager in construction project while for second section are rank all the entire success factor to be an excellent project manager.The data from the questionnaire was analyzed by using mean average index method.Finally from the research and questionnaires that have been done automatically can find factor to be an excellent project manager in construction project.